Prevalence of stigma among patients with schizophrenia: a multi-country systematic review and meta-analysis - Wang, Xianhua; Hu, Jiangli; Wang, Xiaoxia; Liu, Jing; Wang, Yunqiong (Frontiers in Psychology, 2025)
ObjectiveThis study aims to systematically assess the current prevalence of stigma experienced by individuals with schizophrenia and to provide evidence that can inform the development of effective intervention strategies.MethodsA systematic search was conducted in PubMed, Embase, Ovid, Web of Science, Cochrane Library, CINAHL, CNKI, Wanfang, VIP, and CBM databases to identify studies on stigma in schizophrenia patients from their inception up to November 2024. Two independent researchers performed literature screening, data extraction, and quality assessment. Meta-analysis was carried out using Stata 17.0.ResultsFourteen studies encompassing a total of 1,872 schizophrenia patients were included in the analysis. The pooled prevalence of stigma was 75.3% (95%CI:0.690 − 0.816). Subgroup analyses revealed the following rates: Region: Asia 79.6% (95%CI:0.752 − 0.841), Africa 49.9% (95%CI:0.460 − 0.538); Assessment tool: PDD 83.9% (95%CI:0.814 − 0.864), ISMI 73.9%(95%CI:0.665 − 0.814); Publication year: 2018-2024 year 80.8% (95%CI:0.737 − 0.878), 2014-2017 year 69.7%(95%CI:0.595 − 0.800); Age: >60 years 79.5%(95%CI:0.767 − 0.824), 18-60 years 74.2% (95%CI:0.662 − 0.821); Disease stage: Remission phase 75.8% (95%CI:0.679 − 0.836), Stable phase 74.1% (95%CI:0.635 − 0.848); Sample size: >200 cases 73.4% (95%CI:0.652 − 0.816), ≤ 200 cases 80.2% (95%CI:0.731 − 0.873). Sensitivity analysis using the leave-one-out method demonstrated stable pooled effect sizes. Egger's test (P = 0.08) suggested a low risk of publication bias.ConclusionThe prevalence of stigma among individuals with schizophrenia is substantial and influenced by region, assessment instruments, age, stage of illness, and sample size. The subgroup analysis indicated a higher prevalence of stigma associated with the following factors: studies conducted in Asia, the use of the PPD scale, publication after 2018, participants aged > 60 years, Sample size: ≤ 200 cases and patients in the remission stage. Future efforts should prioritize developing culturally adapted interventions specifically aimed at reducing stigma, enhancing social functioning, and improving patients' quality of life.Systematic review registrationPROSPERO, identifier: CRD42024590215.